Assessment of Wire Offset While Machining EN-24 on WEDM - Rizvi, Dr. Syed Asghar Husain; Verma, Durgesh; Kisan, Unni (International Journal of Integrated Engineering, 2024)
Wire offset is the dimensional shift that is experienced while machining a job on Wire-EDM machine. This modeling of wire offset during machining of EN-24 (EN is Euro Norm) was performed implementing Response Surface Methodology (RSM). Factors under consideration are peak current, on duration and off duration of pulse. Scanning Electron Microscopy was later performed for measurement of dimensional shift experienced under various machining conditions. The difference of programmed width and actual width obtained revealed the wire offset of the machined specimen. The tests revealed that Wire-EDM (Wire-Electro Discharge Machine) variables and Wire Offset can be modelled using Quadratic equations. ANOVA (Analysis of Variance) depicted that quadratic term of peak current is crucial parameter for Wire offset trailed by off duration. Keeping medium level of electrical parameters will lead to lower wire offset. Further model validation was performed and the residual error for Wire Offset was found to be 2.43% which suggest the competence of the present model.